PENGEMBANGAN NILAI NILAI BELIAN BERUBAH SEBAGAI METODE PENGURANGAN KEJENUHAN DALAM PROSES MENGHAFAL ALQURAN DI PONDOK PESANTREN IBNU KATSIR 2 JEMBER - Wal Ula Mashithoh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to overcome various kinds of problems experienced by santri by developing local cultural values originating from the East Kalimantan area, namely belian betuah which researchers will later develop through modules that can be used as a reference in overcoming these problems. The specific aim of this research is so that students at PPA Ibnu Katsir can overcome boredom by using local cultural values which will be developed by researchers, and can be used as a means for development in further research. Burnout is an emotional condition when someone feels tired and fed up both mentally and physically due to work demands related to rote memorization, this often happens in Islamic boarding school environments, especially in Islamic boarding school environments, therefore this must be eradicated, by means of the need for guidance - guidance and motivation that can raise the enthusiasm of students in carrying out their mandate as students memorizing the Koran at PPA Ibnu Katsir 2 Jember. Therefore, researchers will distribute questionnaires, make observations and interviews. Researchers conducted research by developing local cultural values which can be useful for overcoming problems in the santri environment, namely in the process of memorizing the Al'Quran by developing local cultural values, namely belian betulah which originates from the Kalimantan area.